LXR agonist inhibits inflammation through regulating MyD88 mRNA alternative splicing - Li, Ni; Li, Yan; Han, Xiaowan; Zhang, Jing; Han, Jiangxue; Jiang, Xinhai; Wang, Weizhi; Xu, Yang; Xu, Yanni; Fu, Yu; Si, Shuyi (Frontiers in Pharmacology, 2022)
Liver X receptors (LXRs) are important regulators of cholesterol metabolism and inflammatory responses. LXR agonists exhibit potently anti-inflammatory effects in macrophages, which make them beneficial to anti-atherogenic therapy. In addition to transrepressive regulation by SUMOylation, LXRs can inhibit inflammation by various mechanisms through affecting multiple targets. In this study, we found that the classic LXR agonist T0901317 mediated numerous genes containing alternative splice sites, including myeloid differentiation factor 88 (MyD88), that contribute to inflammatory inhibition in RAW264.7 macrophages. Furthermore, T0901317 increased level of alternative splice short form of MyD88 mRNA by down-regulating expression of splicing factor SF3A1, leading to nuclear factor κB-mediated inhibition of inflammation. In conclusion, our results suggest for the first time that the LXR agonist T0901317 inhibits lipopolysaccharide-induced inflammation through regulating MyD88 mRNA alternative splicing involved in TLR4 signaling pathway.